Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Produktivitas Karyawan Pada Usaha Kerajinan Gerabah Desa Kasongan Bantul Yogyakarta - Yulianto - AKPAR BSI Yogyakarta (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2012)
ABSTRACT - Any organization or company would like to achieve the goal. To achieve these objectives the role of human resources involved are very important for human resource mengerakan to fit the desired company, it should be understood motivation and job satisfaction of employees, while the methods used in the preparation of this paper is a quantitative method of data collection techniques through observation, interviews and questionnaires.The results of this study are implemented that the value of the constant α = -4.338. This means that if the independent variables (X1 and X2) are assumed to be zero then the productivity of the employees of -4.338. If other variables held constant, the regression coefficient of job satisfaction variables (X1) of 0.231. This means that job satisfaction variable positive effect on employee productivity so that if other variables held constant then the productivity will be increased by 0.231. Motivation variable regression coefficient (X2) of 0.541, this means that the variables of work motivation positive effect on employee productivity so that if other variables held constant then the productivity will increase by 0.541. Motivation (X2) has a greater influence of job satisfaction (X1) on employee productivity. This is evidenced by koefisein P value of 0.541 motivation is greater than the value of job satisfaction that is equal to 0.231.Two independent variables choose the t-test based on the results of work motivation variables apparently greater influence of job satisfaction on work productivity (R2) of 0.397. That is 39.7%. Job satisfaction and motivation variables can explain the dependent variable. While the rest of 61.3% caused by other faktors outside the model.Keywords: Motivation, Satisfaction, Productivity